Frequency-Dependent Cannabinoid Receptor-Independent Modulation of Glycine Receptors by Endocannabinoid 2-AG - Lozovaya, Natalia (Frontiers Research Foundation, 2011)
Endocannabinoids are known as retrograde messengers, being released from the postsynaptic neuron and acting on specific presynaptic G-protein-coupled cannabinoid (CB) receptors to decrease neurotransmitter release. Also, at physiologically relevant concentrations cannabinoids can directly modulate the function of voltage-gated and receptor-operated ion channels. Using patch-clamp recording we analyzed the consequences of the direct action of an endocannabinoid, 2-arachidonoylglycerol (2-AG), on the functional properties of glycine receptor channels (GlyRs) and ionic currents in glycinergic synapses. At physiologically relevant concentrations (0.1–1 μM), 2-AG directly affected the functions of recombinant homomeric α1H GlyR: it inhibited peak amplitude and dramatically enhanced desensitization. The action of 2-AG on GlyR-mediated currents developed rapidly, within ∼300 ms. Addition of 1 μM 2-AG strongly facilitated the depression of glycine-induced currents during repetitive (4–10 Hz) application of short (2 ms duration) pulses of glycine to outside-out patches. In brainstem slices from CB1 receptor knockout mice, 2-AG significantly decreased the extent of facilitation of synaptic currents in hypoglossal motoneurons during repetitive (10–20 Hz) stimulation. These observations suggest that endocannabinoids can modulate postsynaptic metaplasticity of glycinergic synaptic currents in a CB1 receptor-independent manner.